ANALISIS TINGKAT MASLAHAH BAGI KONSUMEN PADA WARUNG PRASMANAN DENGAN KONSEP ALL YOU CAN EAT DI WATAMPONE (Studi Pada Ibu-ibu Milenial) - Aziza, Andi Rezky Nur; Syaparuddin, Syaparuddin (Institut Agama Islam Negeri (IAIN) Bone, 2023)
AbstractThis study aims to analyze the level of maslahah for consumers of millennial mothers who live in Watampone by using the Theory of Planned Behavior. This study uses a quantitative approach for its methodological aspects and Islamic economics for its scientific aspects. To realize these two approaches, the caring variable maslahah is used as an intervening variable in determining purchasing decisions. This study uses data in the form of a questionnaire (questionnaire), and is also supported by interview data and documentation to strengthen the research results. From the results of distributing the questionnaire (questionnaire), as many as 100 questionnaire data were successfully filled in by respondents and analyzed using the SEM approach, the PLS-Path Modeling approach through the Smart-PLS statistical application version 3.3.3